The Semi-Discrete Diffusion Convection Equation with Decay - Lizama-Yanez, C (Elsevier Ltd, 2024)
In this paper we find the fundamental solution of the semi-discrete diffusion convection equation with decay, and we show that under a certain combination of the parameters of the equation said fundamental solution constitutes a uniformly continuous semigroup of operators in the Lebesgue spaces ℓp(Z),1≤p≤∞. © 2024 Elsevier Ltd